Perpetual flight with a small solar-powered UAV: Flight results, performance analysis and model validation - Oettershagen, Philipp; Melzer, Amir; Mantel, Thomas; Rudin, Konrad; Stastny, Thomas; Wawrzacz, Bartosz; Hinzmann, Timo; Alexis, Kostas; Siegwart, Roland (2016 IEEE Aerospace Conference, 2016)
This paper presents the design of the small-scale hand-launchable solar-powered AtlantikSolar UAV, summarizes flight results of a continuous 28-hour solar-powered flight that demonstrated AtlantikSolar's capability for energetically perpetual flight, and offers a model-based verification of flight performance and an outlook on the energetic margins that can be provided towards perpetual flight given today's solar-powered UAV technology. AtlantikSolar is a 5.6m-wingspan and 6.9kg mass low-altitude long-endurance UAV that was designed to provide perpetual endurance at a geographic latitude of 45N in a 4-month window centered around June 21st. A specific design emphasis is robust perpetual endurance with respect to local meteorological disturbances (e.g. clouds, winds, downdrafts). Providing the necessary energetic safety margins is a significant challenge on small-scale solar-powered UAVs. This paper thus describes the design optimizations undertaken on the AtlantikSolar UAV for maximum energetic safety margins. In addition, this paper presents the flight test results, analysis and performance verification of AtlantikSolar's first perpetual endurance continuous 28-hour flight. The flight results show a minimum state-of-charge of 40% or excess time of 7 hours during the night. In addition, the charge margin of 5.9 hours indicates sufficiently-fast battery charging during the day. Both margins exceed the performance of previously demonstrated solar-powered LALE UAVs. Another centerpiece of the paper is the verification of these flight results with the theoretical structural-, aerodynamics- and power-models that were developed and used to conceptually design the UAV. The solar-power income model is extended to take into account solar-panel temperature effects, the exact aircraft geometry and the current orientation and is compared against flight results. Finally, the paper provides an analysis and overview into under what conditions and with which energetic margins perpetual flight is possible with today's battery- and solar-cell technology. A perpetual endurance window of up to 6 months around June 21st is predicted at northern latitudes for the AtlantikSolar UAV configuration without pay-load. A final outlook into first perpetual endurance applications shows that perpetual flight with miniaturized sensing payloads (small optical and infrared cameras) is possible with a perpetual flight window of 4-5 months.